2012
DOI: 10.1186/ar3844
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of lupus: a functional perspective

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease with a strong genetic component and is characterized by chronic inflammation and the production of anti-nuclear auto-antibodies. In the era of genome-wide association studies (GWASs), elucidating the genetic factors present in SLE has been a very successful endeavor; 28 confirmed disease susceptibility loci have been mapped. In this review, we summarize the current understanding of the genetics of lupus and focus on the strongest associated risk loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 113 publications
0
114
0
2
Order By: Relevance
“…Family studies indicate 66% heritability, and the concordance rate in monozygotic and dizygotic twins is in the range of 24-69% and only 2-5% (ref. 64 ), respectively. although genome-wide association studies (GWas) reliably determine sle risk locations, some genetic predisposing factors may differ between populations.…”
mentioning
confidence: 98%
“…Family studies indicate 66% heritability, and the concordance rate in monozygotic and dizygotic twins is in the range of 24-69% and only 2-5% (ref. 64 ), respectively. although genome-wide association studies (GWas) reliably determine sle risk locations, some genetic predisposing factors may differ between populations.…”
mentioning
confidence: 98%
“…Then two days later a process started of their replacing by IgG synthesizing plasmocytes, thereby after two weeks IgG antibodies began to prevail. It is known that individuals with a low threshold for activation of B lymphocytes are susceptible to autoimmune diseases [39]. Computational experiment with reduced activation threshold leads to a strong immune reaction even in the case of single injection of low dose of antigen.…”
Section: Numerical Methods and Program Implementationmentioning
confidence: 99%
“…Recently genome-wide association studies have identified predisposition to Th17 immune response in patients with systemic lupus erythematosus (which is a severe autoimmune disease) [39]. To examine the role of Th17 in this disease a special extension of the model has been made.…”
Section: Increased Expansion Of B Lymphocytes Under the Action Of Th1mentioning
confidence: 99%
“…The genetic heritability of SLE is approximately 66%. Genome wide association studies have mapped of 28 disease susceptibility loci which account for not more than10% of the genetic heritability (Guerra et al;2012). Certain major histocompatibility complex class II (MHCII) alleles, such as: HLA-DRB* 0301 and DRB1* 1501, are involved in genetic susceptibility to SLE (Fernando et al;.…”
Section: Introduction:-mentioning
confidence: 99%